Regional media in the digital age of journalism: sociological research - Hradziushka, Aleksandr A. (Journal of the Belarusian State University. Journalism, 2019)
The results of the study of the current state of the regional media sphere in a digital environment are presented. 85 heads of regional media were interviewed in six regions of the Republic of Belarus. The subject of the sociological research was the forecasts and opinions of influential managers on the development strategies of state district newspapers in the online environment. As a result of the survey, a comprehensive assessment of the effectiveness of local media support on the Internet was given. The role of the mobile Internet in the transformation of the media space is shown. The question of new forms and technologies of interaction between newspapers and the audience has been updated. The most successful examples of digital transformations of regional media are considered. It was found that, under the influence of new technology, the work of journalists in editorial offices has changed dramatically. The main factors that contribute to or hinder the development of state-owned newspapers on the Internet are identified. As a result of the research, it was established that digitalization significantly changes the system characteristics of regional media and can lead to a radical change in the Belarusian media industry in the long term.
Keywords: regional journalism; hyper localization; regional identity; digital media; mobile Internet; media management